Laser ablation of pristine Fe foil for constructing a layer-by-layer SiO2/Fe2O3/Fe integrated anode for high cycling-stability lithium-ion batteries. Issue 17 (22nd April 2021) - Zhang, Zhongyuan; Yang, Chen; Fang, Canfeng; Yang, Wenfei; Zhang, Xue; Rong, Zhiguo; Li, Xiyang; Jung, Youngguan; Lu, Jing; Dong, Xinglong
Abstract : An integrated SiO2 /Fe2 O3 /Fe anode is fabricated by a laser ablation technique, traced by on-line optical emission spectroscopy (OES) diagnosis. The integrated structure together with the SiO2 coating layer greatly improves the cycling stability. Abstract : In this paper, an integrated SiO2 /Fe2 O3 /Fe anode is fabricated by straightforward laser ablation of the surface of Fe foil in air. The oxidized surface is subsequently coated with tetraethyl orthosilicate (TEOS) and transformed into a SiO2 layer through a calcination process in an argon atmosphere. The surface oxidation is traced by on-line optical emission spectroscopy (OES) diagnosis. With high electron temperature (∼5200 K) in the laser irradiation zone, the nanostructured Fe2 O3 layer is formed on the Fe foil, resulting in the pristine Fe2 O3 /Fe anode. This greatly simplified procedure with respect to the conventional route allows direct connection between the Fe2 O3 layer and the Fe substrate (current collector) without any binder or conductive agent. In addition, the SiO2 coating layer greatly improves the cycling stability due to the compensatory contribution to capacity during the cycling process and its compatible elasticity to accommodate the volume expansion of Fe2 O3, which is verified by first-principles theoretical calculations. The integrated SiO2 /Fe2 O3 /Fe anode delivers a stable capacity of 651.7 mA h g −1 at 0.2 A g −1 after 100 cycles. This strategy offers a low-cost route for the rapid fabrication of integrated electrodes, broadening their applications in high cycling-stability LIBs.